Congenital Cardiac Surgery and Parental Perception of Risk: A Quantitative Analysis. Issue 6 (November 2019) - Lotto, Robyn; Jones, Ian; Seaton, Sarah E.; Dhannapuneni, Ram; Guerrero, Rafael; Lotto, Attilio
Introduction: Interpretation of risk by parents of children undergoing congenital cardiac surgery is poorly documented. The available evidence highlights a dichotomy where clinicians suggest parents may not grasp the complexity and risk associated with procedures, while some parents suggest risk is unnecessarily overemphasized. Aim: To quantify how risk is perceived by parents. Methods: One hundred six parents of children undergoing cardiac surgery were recruited and completed a Likert-type scale from 1 (perceived low risk) to 6 (perceived high risk), at 5 points: arrival at preadmission, post discussion with anethetist/surgeon, day of surgery, discharge from intensive care, and at outpatient follow-up. The surgical sample was stratified according to Risk Adjustment in Congenital Heart Surgery level. Analysis: Data were analyzed using Wilcoxon rank tests for differences in distributions of scores and Krippendorff α to examine the level of agreement. Results: Median parental risk scores varied over time, with no consistent risk scores observed. Maternal scores were consistently higher than paternal scores at every time point ( P < .001). Postoperative complications resulted in a persistent rise in risk perception at follow-up ( P < .001). Analysis of parental risk scores and objective measures of surgical risk highlighted poor agreement that was particularly marked at the extremes of risk. Conclusions: Parents perceived higher risk scores than those reported by the clinical team. Mothers reported statistically significantly higher scores than their partners, highlighting potential tensions. In addition, the changing perception of risk over time emphasizes the need for flexible levels of support and information as parents navigate uncertainty.